DOSES OF PHOSPHORUS AND POTASSIUM IN PEANUT PLANT IN THE PRESENCE AND ABSENCE OF FOLIAR FERTILIZATION - Meneghette, H. H. A.; Lazarini, E.; Bossolani, J. W.; Parra, L. F.; Hayashi, F. K. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Wishing to evaluate agronomic performance of peanut crop submitted to different doses of phosphorus and potassium together with the presence and absence of application of leaf fertilizer, 2 experiments were developed on Fazenda de Ensino, Pesquisa e Extensão/UNESP - Ilha Solteira Campus, located in the municipality of Selvíria – MS. The experimental design used was in randomized blocks with 4 replicates, Being the treatments arranged in factorial scheme 3 x 3 x 2, being 3 doses of phosphor (0, 60 e 120 kg ha-1 de P2O5) and 3 doses of potassium (0, 20 e 40 kg ha-1 de K2O) by way of soil, and absence or presence of leaf fertilizer Flonergan® (1 L ha-1). The cultivar used was the IAC-Tatu ST, with spacing of 0,9 m. With sowing performed in June 16 and November 14, 2006 for the Experiment 1 and 2, respectively. For Experiment 1, the mass parameter of 100 grains presented significant interaction or doses of phosphorus x foliar fertilizer, especially the treatment constituted by the presence of foliar fertilizer at the dose of 60 kg ha-1 P2O5. In Experiment 2, it is observed that the dose of 20 kg ha-1 of K20 caused a larger increase in the mass of 100 grains. No increase in peanut grain yield was observed until the doses of phosphorus and potassium used.